STRATEGI KENDALI ORGANISASI COFFEE SHOP DALAM MENINGKATKAN KUALITAS PRODUK TERHADAP MINAT PELANGGAN (Studi Kasus Team Kinerja “TALK BOGOR”) - Salomon A.M. Babys; Raden Cahyo Prabowo (Oratio Directa (Prodi Ilmu Komunikasi), 2021)
Abstract The increasing role of the coffee industry is accompanied by a rapid increase in the demand for coffee. It is observed that it has a weakness in the amount of coffee capacity which is still not evenly distributed and is not able to meet the existing demand in Indonesia. There are challenges for companies to survive and renew their competitive strategies. This study aims to find out the competitive strategy applied by the company today and try to formulate the company's blue ocean competitive strategy. In collecting data using interview and observation methods. Determination of interview sources using purposive sampling technique. The data obtained was then tested for the validity of the data using source triangulation. Research on the Coffee Shop Organizational Strategy in team performance Quality Against Customer Interests (Case Study of the "Talk Bogor" Performance Team) at Talk Bogor in team performance improving the quality of customer interest has the aim of knowing how the Control Strategy Coffee Shop Organization in Improving Product Quality for Customer Interests (Case Study of “Talk Bogor” Performance Team) at Talk Bogor. The theories used in this research include the Organizational Control Theory of Philip Tompkins and colleagues. The research paradigm is Post-positivism. This research approach is qualitative by using case study research method. this study are the Coffee Shop Organizational Control Strategy in Team Kinerja Quality for Customer Interests (Case Study of the "Talk Bogor" Performance Team) at Talk Bogor which is good and quality by means of two-way communication between Achmed H Edinbur and the Talk Bogor performance team and dialogue together so that customers' interest in TALK Bogor becomes quality & develops rapidly. In this TALK Bogor Coffee Shop, to improve the quality of customers, the research team held a dialogue with Achmed H Edinbur regarding input, suggestions on what to improve in this coffee shop so that more customers, the business develops to advance this TALK Bogor.Keywords Strategy, Organizational Control,Marketing Communication, Product Quality, Customer Interest, Case Study